Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/catal12121556
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Generation from Aqueous Methanol Solution over n-Butylamine-Intercalated Layered Titanate H2La2Ti3O10: Activity and Stability of the Hybrid Photocatalyst

Abstract: The stability of platinized n-butylamine-intercalated layered titanate H2La2Ti3O10 during the process of photocatalytic hydrogen production from aqueous methanol under UV irradiation has been thoroughly investigated by means of XRD, CHN, TG, 13C NMR, BET, SEM and GC-MS analysis. It was revealed that n‑butylamine completely abandons the interlayer space and transforms into n‑butyraldehyde within 3 h of the reaction, while the particle morphology and specific surface area of the photocatalyst are preserved. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Although the synthesis of isostructural hybrids with unbranched amines and alcohols is not particularly difficult and similar compounds are known for many classes of layered oxides, these compounds can serve as precursors for the formation of hybrids with more complex organic molecules. In addition, even such relatively simple systems can exhibit significant physicochemical properties; in particular, it has been shown that hybrid compounds based on normal alcohols and amines exhibit a significantly increased photocatalytic activity in comparison with unmodified analogues in the reaction of hydrogen evolution from aqueous solutions [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All this makes the preparation and study of such compounds an urgent task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the synthesis of isostructural hybrids with unbranched amines and alcohols is not particularly difficult and similar compounds are known for many classes of layered oxides, these compounds can serve as precursors for the formation of hybrids with more complex organic molecules. In addition, even such relatively simple systems can exhibit significant physicochemical properties; in particular, it has been shown that hybrid compounds based on normal alcohols and amines exhibit a significantly increased photocatalytic activity in comparison with unmodified analogues in the reaction of hydrogen evolution from aqueous solutions [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All this makes the preparation and study of such compounds an urgent task.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the reactivity of the protonated niobate HSr 2 Nb 3 O 10 ∙yH 2 O with organic substances has not been sufficiently studied, except for some of the papers presented above. However, the formation of its organically modified derivatives deserves special attention since the inorganic–organic hybrids based on layered perovskite-like oxides are of high interest as high-performance photocatalytic materials for hydrogen production and water purification, outperforming the initial compounds in the activity up to several orders of magnitude [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…% aqueous methanol over ZnCr-and NiCr-LDHs are 88 µmol•h −1 •g −1 (φ = 0.013%) and 41 µmol•h −1 •g −1 (φ = 0.0062%), respectively. Undoubtedly, these compounds demonstrate relatively low performance in comparison with the layered oxide photocatalysts tested earlier under the same conditions [98,[102][103][104][105][106][107][108][109]. However, the LDHs under study differ from the aforementioned layered oxides in their intrinsic absorption of visible light, which may make them promising light-sensitive components of composite photocatalysts.…”
Section: Photocatalytic Activity Of Zncr-and Nicr-ldhsmentioning
confidence: 92%
“…% aqueous methanol was studied for 5 samples of each LDH with a different crystallite size (Table 2). The experiments were carried out under both ultraviolet irradiation (DRT-125 mercury lamp, 125 W, λ > 220 nm) and purely visible light (LED source, 100 W, λ = 425 nm) in the photocatalytic laboratory setting used in our previous reports [98,[102][103][104][105][106][107][108][109] and described in detail in Information S1. The spectra of the light sources are shown in Figure S4.…”
Section: Investigation Of Photocatalytic Activitymentioning
confidence: 99%
“…Photocatalysis is a unique approach that is widely used and utilized in many various fields of study, including the removal of dangerous inorganic and organic pollutants from wastewater, the purification of contaminated air, the elimination of pesticides, and others [36][37][38][39][40]. Zinc oxide (ZnO) is prominent material in the field of photocatalysis for environmental management system.…”
Section: Introductionmentioning
confidence: 99%